The study of Radioactivity in soil samples from region AL-Heara in Al-Najaf Al-Ashraf Government - Ali K. H; Ikhlas H.K (Al-Qadisiyah Journal of Pure Science, 2017)
The soil is one of the most important sources of ionizing radiation posed to natural rights as the natural radioactive nuclides , such as uranium-238 series nuclides as well as a series of thorium-232 in addition to the isotope potassium -40 , exist in abundance in the soil which in one way or another affect on human health so it was the study of radioactivity in soil center region AL-Heara in Al-Najaf Al-Ashraf Government , in order to determine the effect of radiation on this soil and thus on human health. has been selected ( 20 ) locations sampling center of region AL-Heara and collected from each site two samples of the first sample from surface soil (0-5)cm and The second in depth(5-20)cm to be number of samples which assayed(40)sample and The gamma rays spectral measurements were done for all samples by using Iodide Sodium activated by Thalium NaI(Tl),its dimension3"× 3".It was found that the radioactivity of potassium 40K , uranium 238U and thorium 232Th in the models studied between (13.12 ± 4.67) to (489.34 ± 8.14 ( Bq per kg and average (275.76 ± 6.37(Bq per kg , (0.52 ± 1.16) to (31.17 ± 2.26 Bq ( per kg and average (13.44 ± 1.75(Bq per kg and (3.19 ± 1.06) to (44.79 ± 1.74( Bq per kg and average (15.17 ± 1.19 (Bq per kg , respectively , and indicated these results to The radioactivity within the permissible limits globally. The values of the Radium equivalent , absorbed dose , risk coefficients and annual effective dose of internal and external effectiveness and concentration coefficient with which the was calculated is within the allowable limits globally